DNAR-11. CHARACTERIZING THE GENOMIC CONSEQUENCES OF G-QUADRUPLEX STABILIZATION IN ATRX-DEFICIENT HIGH-GRADE GLIOMA. (14th November 2022) - Dharmaiah, Sharvari; Chen, Brandon; Malgulwar, Prit Benny; Tadimeti, Vasudev; Farooqi, Ahsan; Huse, Jason
Abstract: α-thalassaemia/mental retardation X-linked (ATRX) mutations are a critical molecular marker for high-grade glioma (HGG). These mutations lead to accumulations of abnormal DNA secondary G-quadruplex (G4) structures, thereby inducing replication stress and DNA damage. As G4s arise at GC-rich regions (i.e., pericentromeric and telomeric regions), ATRX-deficiency alters genome-wide accessibility of chromatin and causes transcriptional dysregulation. However, the genomic consequences of this in the context of ATRX-deficiency are poorly understood. Our goal is to target ATRX deficiency through G4 stabilizers, a class of novel small molecule compounds that selectively bind to and stabilize G4s. Using a combination of functional experiments such as cell viability, western blot, flow cytometry, RNA-sequencing (RNA-seq), and immunofluorescence (IF), we evaluated the mechanisms that drive selective lethality upon G4 stabilization. Patient-derived glioma stem cells (GSCs) were treated with either vehicle (DMSO) or varying doses of CX-5461 (G4 stabilizer, Senhwa Biosciences). Excitingly, ATRX-deficient GSCs demonstrate dose-dependent enhanced sensitivity to G4 stabilization, compared to ATRX-intact and vehicle controls. Cell viability assays confirmed the specificity of CX-5461 in comparison to other commercially used G4 stabilizers. G4 stabilization activated p53-independent apoptosis and exhibited G2/M arrest in ATRX-deficient GSCs and, interestingly, upregulated expression of both ATR and ATM pathways, indicating enhanced replication stress and DNA damage, respectively. IF staining confirmed enhanced induction of replication stress and DNA damage markers 53BP1 and gH2AX. Our preliminary findings suggest that ATR and ATM activation leads to Cyclin D1 degradation and inhibition of transcription factor NF-κB, thereby driving apoptosis. In fact, RNA-seq analyses revealed positive enrichment of apoptosis, DNA repair, and NF-κB pathways and negative enrichment of the G2/M checkpoint in ATRX-deficient GSCs treated with CX-5461. Our work defines mechanisms of action and efficacy of a novel therapeutic strategy for pre-clinical ATRX-deficient HGG models, with strong implications for other ATRX-deficient cancers and potential translation into clinical practice.